Thiophene Derivatives as Ligands for Highly Luminescent and Stable Manganese-Doped CsPbCl3 Nanocrystals - Wang, Qian; Gao, Long; Yu, Chenxi; Wang, Meng; Gou, Lijie; Zhang, Jiaqi (Frontiers in Chemistry, 2022)
Ligands on the surface of perovskite nanocrystals are important to stabilizing the nanocrystal structure. However, the research of ligands on Mn2+ ion doped CsPbCl3 nanocrystals (Mn: CsPbCl3 NCs), a promising candidate family for lightning community, is relatively rare. Here, we demonstrate a new ligand modification strategy for preparing high-quality Mn: CsPbCl3 NCs by a simple hot-injection method. Thiophene derivative, for the first time, is applied as ligands for perovskite nanocrystals. The new ligands of thiophene derivatives passivate defects on the surface of NCs and enhance optical properties, originating from the sulfur in thiophene additives binding to the uncoordinated lead ions. The photoluminescence quantum yield of the modified Mn: CsPbCl3 NCs is 93% in comparison with 46% of the pristine counterparts, which value is the highest to date for ligand modified Mn: CsPbCl3 NCs. Meanwhile, the thermal, storage, and purification stability are also significantly improved. The performance of related LEDs is also investigated.